Anti-aging corrosion-resistant flexible graphene cable
By using graphene oxide and zinc oxide composite particles in the cable material, and forming an organic copolymer layer through silane coupling agent modification and copolymerization reaction, the problem of insufficient corrosion resistance and mechanical properties of existing cable materials is solved, and higher corrosion resistance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411859944.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing cable materials have insufficient corrosion resistance and mechanical properties when facing oil stains, chemicals and mechanical wear, resulting in aging and degradation of performance.
Graphene oxide and zinc oxide composite particles are used to modify them through silane coupling agent, vinyl groups are introduced, and they participate in the copolymerization reaction of styrene, sorbic acid and oleic acid to form a coated structure of an organic copolymer layer coated with inorganic filler, enhancing the binding force and dispersion of the composite particles and the polyethylene system.
It significantly improves the mechanical properties and corrosion resistance of the material, extends the service life of the cable and enhances its reliability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables and relates to an aging-resistant and corrosion-resistant flexible graphene cable. Background Art
[0002] In actual applications, cables may come into contact with a variety of oils, chemicals, and be subjected to mechanical wear. Therefore, they must have excellent corrosion resistance, high strength, and bending resistance. The high-strength performance is intended to prevent the cable sheath from being quickly worn out due to frequent friction, thereby effectively avoiding the exposure of the internal conductor and the possible risk of short circuits. The enhanced bending resistance ensures that the cable can maintain its structural integrity and electrical performance stability even under extreme bending conditions, which is of immeasurable importance for maintaining the continuous operation and safety of the automation system.
[0003] The outer layer of the cable is generally made of polyethylene, which is a cheap, lightweight, non-toxic general-purpose plastic. It has the disadvantages of being brittle at low temperatures, low mechanical strength and hardness, large molding shrinkage, poor toughness, poor corrosion resistance, easy aging and poor heat resistance.
[0004] As a new type of two-dimensional material, graphene has been widely used in polyethylene cable protection materials due to its unique physical and chemical properties. The addition of graphene significantly improves the mechanical properties and corrosion resistance of polyethylene cable protection materials. Due to its high strength and high modulus characteristics, graphene improves the deformation resistance of polyethylene cable protection materials, extends the service life of the cable and enhances its reliability. At the same time, the corrosion resistance of graphene protects the cable from chemical corrosion and maintains its performance in harsh environments. However, graphene has a high production cost and poor dispersion in polyethylene materials, which affects the uniform distribution and overall performance of the material, limiting its ability to improve mechanical properties and corrosion resistance. Summary of the invention
[0005] The purpose of the present invention is to provide an aging-resistant and corrosion-resistant flexible graphene cable. The present invention utilizes graphene oxide and zinc oxide composite particles, which are then modified by a silane coupling agent, and vinyl is introduced into the surface of the composite particles to participate in the copolymerization reaction of styrene, sorbic acid and oleic acid to form an organic copolymer layer coating an inorganic filler coating structure, thereby enhancing the bonding force and dispersibility of the composite particles and the polyethylene system, and improving the mechanical properties and corrosion resistance of the material.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A flexible graphene cable that is resistant to aging and corrosion, comprises a conductive wire group, a metal shielding layer and a protective layer, wherein the metal shielding layer covers the conductive wire group, and an elastic material is filled between the metal shielding layer and the conductive wire group; the protective layer is arranged on the outer surface of the metal shielding layer; the preparation of the graphene cable comprises covering the conductive wire group with the metal shielding layer, and melt-extruding the molten protective layer on the outer surface of the metal shielding layer.
[0007] The protective layer comprises the following components by weight: 90-100 parts of high-density polyethylene, 12-16 parts of modified graphene and 2-3 parts of other additives.
[0008] As a preferred technical solution of the present invention, the other additives are mixed by an anti-UV agent, a lubricant and an antioxidant in a mass ratio of 2.0-2.3:3.5-4.0:2.2-2.6; the anti-UV agent is one or two of UV-9 and BP-6; the lubricant is oxidized polyethylene wax; the antioxidant is one or more of antioxidant 168, antioxidant 1010, antioxidant 1076 and antioxidant 1098.
[0009] As a preferred technical solution of the present invention, the method for preparing the modified graphene comprises the following steps: 1) In an inert atmosphere, slowly drop a zinc nitrate aqueous solution and a sodium hydroxide aqueous solution into graphene oxide to adjust the pH value, filter, wash, and vacuum dry to a constant weight to obtain composite particles; 2) The composite particles and anhydrous ethanol are mixed and preheated, and the silane coupling agent is added dropwise and then stirred continuously, centrifuged, washed, and vacuum dried to constant weight to obtain modified composite particles; 3) Under an inert atmosphere, the modified composite particles and anhydrous ethanol are ultrasonically mixed, sorbic acid, styrene and oleic acid are added and mixed, an initiator is added and heated and stirred, and after cooling to room temperature, the mixture is centrifuged and vacuum dried to constant weight to obtain modified graphene.
[0010] As a preferred technical solution of the present invention, in step 1), the inert atmosphere is a nitrogen atmosphere; the pH value is adjusted to a pH value of 7.0-7.8; the washing is washing with deionized water to neutrality; and the vacuum drying temperature is 80°C.
[0011] As a preferred technical solution of the present invention, in step 1), the mass ratio of the zinc nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 14-16:22-24:7.2-8.0; the concentration of the sodium hydroxide aqueous solution is 8wt%; the concentration of the zinc nitrate aqueous solution is 6wt%.
[0012] As a preferred technical solution of the present invention, in step 2), the preheating temperature is 40°C; the continued stirring is stirring at 50-60°C and 300-400 r / min for 180-240 min; the washing is washing 3 times with anhydrous ethanol; and the vacuum drying temperature is 80°C.
[0013] As a preferred technical solution of the present invention, in step 2), the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 2.0-2.4:20-25:0.4-0.5; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
[0014] As a preferred technical solution of the present invention, in step 3), the inert atmosphere is a nitrogen atmosphere; the ultrasonic treatment is performed at a power of 300-400W for 15-20min; the heating and stirring is performed at a temperature of 60-65°C and a speed of 300-400r / min for 6-8h; and the vacuum drying temperature is 80°C.
[0015] As a preferred technical solution of the present invention, in step 3), the mass ratio of the modified composite particles, anhydrous ethanol, sorbic acid, styrene, oleic acid and initiator is 12-14:40-50:3.2-4.0:1.2-1.6:2.0-2.4:0.16-0.18; the initiator is azobisisobutyronitrile.
[0016] As a preferred technical solution of the present invention, the preparation method of the protective layer comprises mixing high-density polyethylene, modified graphene and other additives for 20-30 minutes, placing in an extruder for melt extrusion at a temperature of 190-210°C, granulating, and molding to obtain the protective layer.
[0017] Beneficial effects of the present invention: The present invention utilizes graphene oxide and zinc oxide composite particles, which are then modified by a silane coupling agent, and vinyl groups are introduced onto the surface of the composite particles, which participate in the copolymerization reaction of styrene, sorbic acid and oleic acid to form a coating structure in which an organic copolymer layer coats an inorganic filler, thereby enhancing the bonding force and dispersibility of the composite particles with a polyethylene system, and improving the mechanical properties and corrosion resistance of the material. DETAILED DESCRIPTION
[0018] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0019] A flexible graphene cable that is resistant to aging and corrosion, comprises a conductive wire group, a metal shielding layer and a protective layer, wherein the metal shielding layer covers the conductive wire group, and an elastic material is filled between the metal shielding layer and the conductive wire group; the protective layer is arranged on the outer surface of the metal shielding layer; the preparation of the graphene cable comprises covering the conductive wire group with the metal shielding layer, and melt-extruding the molten protective layer on the outer surface of the metal shielding layer.
[0020] Example 1 The protective layer comprises the following components by weight: 90 parts of high-density polyethylene, 12 parts of modified graphene and 2 parts of other additives; The other additives are formed by mixing an anti-UV agent, a lubricant and an antioxidant in a mass ratio of 2.0:3.5:2.2; the anti-UV agent is BP-6; the lubricant is oxidized polyethylene wax; and the antioxidant is formed by mixing antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2.
[0021] The preparation method of the modified graphene comprises the following steps: 1) In an inert atmosphere, slowly drop a zinc nitrate aqueous solution and a sodium hydroxide aqueous solution into graphene oxide to adjust the pH value, filter, wash, and vacuum dry to a constant weight to obtain composite particles; 2) The composite particles and anhydrous ethanol are mixed and preheated, and the silane coupling agent is added dropwise and then stirred continuously, centrifuged, washed, and vacuum dried to constant weight to obtain modified composite particles; 3) Under an inert atmosphere, the modified composite particles and anhydrous ethanol are ultrasonically mixed, sorbic acid, styrene and oleic acid are added and mixed, an initiator is added and heated and stirred, and after cooling to room temperature, the mixture is centrifuged and vacuum dried to constant weight to obtain modified graphene.
[0022] In step 1), the inert atmosphere is a nitrogen atmosphere; the pH value is adjusted to 7.0; the washing is washing with deionized water until neutral; the vacuum drying temperature is 80°C; the mass ratio of the zinc nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 14:22:7.2; the concentration of the sodium hydroxide aqueous solution is 8wt%; and the concentration of the zinc nitrate aqueous solution is 6wt%.
[0023] In step 2), the preheating temperature is 40°C; the continued stirring is stirring at 50°C and 300 r / min for 180 min; the washing is washing 3 times with anhydrous ethanol; the vacuum drying temperature is 80°C; the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 2.0:20:0.4; and the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
[0024] In step 3), the inert atmosphere is a nitrogen atmosphere; the ultrasonic treatment is performed at a power of 300 W for 15 minutes; the heating and stirring is performed at a temperature of 60° C. and a speed of 300 r / min for 6 hours; the vacuum drying temperature is 80° C.; the mass ratio of the modified composite particles, anhydrous ethanol, sorbic acid, styrene, oleic acid and initiator is 12:40:3.2:1.2:2.0:0.16; and the initiator is azobisisobutyronitrile.
[0025] The preparation method of the protective layer comprises the following steps: mixing high-density polyethylene, modified graphene and other additives for 20 minutes, placing the mixture in an extruder and melting and extruding the mixture at a temperature of 190° C., granulating the mixture, and molding the mixture to obtain the protective layer.
[0026] Example 2 The protective layer comprises the following components by weight: 92 parts of high-density polyethylene, 13 parts of modified graphene, and 2.2 parts of other additives; The other additives are formed by mixing an anti-UV agent, a lubricant and an antioxidant in a mass ratio of 2.1:3.6:2.3; the anti-UV agent is BP-6; the lubricant is oxidized polyethylene wax; and the antioxidant is formed by mixing antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2.
[0027] The preparation method of the modified graphene comprises the following steps: 1) In an inert atmosphere, slowly drop a zinc nitrate aqueous solution and a sodium hydroxide aqueous solution into graphene oxide to adjust the pH value, filter, wash, and vacuum dry to a constant weight to obtain composite particles; 2) The composite particles and anhydrous ethanol are mixed and preheated, and the silane coupling agent is added dropwise and then stirred continuously, centrifuged, washed, and vacuum dried to constant weight to obtain modified composite particles; 3) Under an inert atmosphere, the modified composite particles and anhydrous ethanol are ultrasonically mixed, sorbic acid, styrene and oleic acid are added and mixed, an initiator is added and heated and stirred, and after cooling to room temperature, the mixture is centrifuged and vacuum dried to constant weight to obtain modified graphene.
[0028] In step 1), the inert atmosphere is a nitrogen atmosphere; the pH value is adjusted to 7.2; the washing is washing with deionized water until neutral; the vacuum drying temperature is 80°C; the mass ratio of the zinc nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 14.5:22.5:7.4; the concentration of the sodium hydroxide aqueous solution is 8wt%; and the concentration of the zinc nitrate aqueous solution is 6wt%.
[0029] In step 2), the preheating temperature is 40°C; the continued stirring is stirring at 52°C and 320 r / min for 190 min; the washing is washing 3 times with anhydrous ethanol; the vacuum drying temperature is 80°C; the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 2.1:21:0.43; and the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
[0030] In step 3), the inert atmosphere is a nitrogen atmosphere; the ultrasonic treatment is performed at a power of 320 W for 16 minutes; the heating and stirring is performed at a temperature of 61° C. and a speed of 320 r / min for 6.5 hours; the vacuum drying temperature is 80° C.; the mass ratio of the modified composite particles, anhydrous ethanol, sorbic acid, styrene, oleic acid and initiator is 12.5:42:3.4:1.3:2.1:0.17; and the initiator is azobisisobutyronitrile.
[0031] The preparation method of the protective layer comprises the following steps: mixing high-density polyethylene, modified graphene and other additives for 22 minutes, placing the mixture in an extruder and melting and extruding the mixture at a temperature of 195° C., granulating the mixture, and molding the mixture to obtain the protective layer.
[0032] Example 3 The protective layer comprises the following components by weight: 95 parts of high-density polyethylene, 14 parts of modified graphene and 2.5 parts of other additives; The other additives are formed by mixing an anti-UV agent, a lubricant and an antioxidant in a mass ratio of 2.2:3.8:2.4; the anti-UV agent is BP-6; the lubricant is oxidized polyethylene wax; and the antioxidant is formed by mixing antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2.
[0033] The preparation method of the modified graphene comprises the following steps: 1) In an inert atmosphere, slowly drop a zinc nitrate aqueous solution and a sodium hydroxide aqueous solution into graphene oxide to adjust the pH value, filter, wash, and vacuum dry to a constant weight to obtain composite particles; 2) The composite particles and anhydrous ethanol are mixed and preheated, and the silane coupling agent is added dropwise and then stirred continuously, centrifuged, washed, and vacuum dried to constant weight to obtain modified composite particles; 3) Under an inert atmosphere, the modified composite particles and anhydrous ethanol are ultrasonically mixed, sorbic acid, styrene and oleic acid are added and mixed, an initiator is added and heated and stirred, and after cooling to room temperature, the mixture is centrifuged and vacuum dried to constant weight to obtain modified graphene.
[0034] In step 1), the inert atmosphere is a nitrogen atmosphere; the pH value is adjusted to 7.4; the washing is washing with deionized water until neutral; the vacuum drying temperature is 80°C; the mass ratio of the zinc nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 15:23:7.6; the concentration of the sodium hydroxide aqueous solution is 8wt%; and the concentration of the zinc nitrate aqueous solution is 6wt%.
[0035] In step 2), the preheating temperature is 40°C; the continued stirring is stirring at 55°C and 350 r / min for 210 min; the washing is washing 3 times with anhydrous ethanol; the vacuum drying temperature is 80°C; the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 2.2:22:0.45; and the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
[0036] In step 3), the inert atmosphere is a nitrogen atmosphere; the ultrasonic treatment is performed at a power of 350 W for 18 minutes; the heating and stirring is performed at a temperature of 62° C. and a speed of 350 r / min for 7 hours; the vacuum drying temperature is 80° C.; the mass ratio of the modified composite particles, anhydrous ethanol, sorbic acid, styrene, oleic acid and initiator is 13:45:3.6:1.4:2.2:0.17; and the initiator is azobisisobutyronitrile.
[0037] The preparation method of the protective layer comprises the following steps: mixing high-density polyethylene, modified graphene and other additives for 25 minutes, placing the mixture in an extruder for melt extrusion at a temperature of 200° C., granulating and molding the mixture to obtain the protective layer.
[0038] Example 4 The protective layer comprises the following components by weight: 98 parts of high-density polyethylene, 15 parts of modified graphene, and 2.8 parts of other additives; The other additives are formed by mixing an anti-UV agent, a lubricant and an antioxidant in a mass ratio of 2.3:3.9:2.5; the anti-UV agent is BP-6; the lubricant is oxidized polyethylene wax; and the antioxidant is formed by mixing antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2.
[0039] The preparation method of the modified graphene comprises the following steps: 1) In an inert atmosphere, slowly drop a zinc nitrate aqueous solution and a sodium hydroxide aqueous solution into graphene oxide to adjust the pH value, filter, wash, and vacuum dry to a constant weight to obtain composite particles; 2) The composite particles and anhydrous ethanol are mixed and preheated, and the silane coupling agent is added dropwise and then stirred continuously, centrifuged, washed, and vacuum dried to constant weight to obtain modified composite particles; 3) Under an inert atmosphere, the modified composite particles and anhydrous ethanol are ultrasonically mixed, sorbic acid, styrene and oleic acid are added and mixed, an initiator is added and heated and stirred, and after cooling to room temperature, the mixture is centrifuged and vacuum dried to constant weight to obtain modified graphene.
[0040] In step 1), the inert atmosphere is a nitrogen atmosphere; the pH value is adjusted to 7.6; the washing is washing with deionized water until neutral; the vacuum drying temperature is 80°C; the mass ratio of the zinc nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 15.5:23.5:7.8; the concentration of the sodium hydroxide aqueous solution is 8wt%; and the concentration of the zinc nitrate aqueous solution is 6wt%.
[0041] In step 2), the preheating temperature is 40°C; the continued stirring is stirring at 58°C and 370 r / min for 220 min; the washing is washing 3 times with anhydrous ethanol; the vacuum drying temperature is 80°C; the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 2.3:24:0.48; and the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
[0042] In step 3), the inert atmosphere is a nitrogen atmosphere; the ultrasonic treatment is performed at a power of 370 W for 19 minutes; the heating and stirring is performed at a temperature of 64° C. and a speed of 370 r / min for 7.5 hours; the vacuum drying temperature is 80° C.; the mass ratio of the modified composite particles, anhydrous ethanol, sorbic acid, styrene, oleic acid and initiator is 13.5:48:3.8:1.5:2.3:0.17; and the initiator is azobisisobutyronitrile.
[0043] The preparation method of the protective layer comprises the following steps: mixing high-density polyethylene, modified graphene and other additives for 28 minutes, placing the mixture in an extruder and melting and extruding the mixture at a temperature of 205° C., granulating the mixture, and molding the mixture to obtain the protective layer.
[0044] Example 5 The protective layer comprises the following components by weight: 100 parts of high-density polyethylene, 16 parts of modified graphene and 3 parts of other additives; The other additives are formed by mixing an anti-UV agent, a lubricant and an antioxidant in a mass ratio of 2.3:4.0:2.6; the anti-UV agent is BP-6; the lubricant is oxidized polyethylene wax; and the antioxidant is formed by mixing antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2.
[0045] The preparation method of the modified graphene comprises the following steps: 1) In an inert atmosphere, slowly drop a zinc nitrate aqueous solution and a sodium hydroxide aqueous solution into graphene oxide to adjust the pH value, filter, wash, and vacuum dry to a constant weight to obtain composite particles; 2) The composite particles and anhydrous ethanol are mixed and preheated, and the silane coupling agent is added dropwise and then stirred continuously, centrifuged, washed, and vacuum dried to constant weight to obtain modified composite particles; 3) Under an inert atmosphere, the modified composite particles and anhydrous ethanol are ultrasonically mixed, sorbic acid, styrene and oleic acid are added and mixed, an initiator is added and heated and stirred, and after cooling to room temperature, the mixture is centrifuged and vacuum dried to constant weight to obtain modified graphene.
[0046] In step 1), the inert atmosphere is a nitrogen atmosphere; the pH value is adjusted to a pH value of 7.8; the washing is washing with deionized water until neutral; the vacuum drying temperature is 80°C; the mass ratio of the zinc nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 16:24:8.0; the concentration of the sodium hydroxide aqueous solution is 8wt%; and the concentration of the zinc nitrate aqueous solution is 6wt%.
[0047] In step 2), the preheating temperature is 40°C; the continued stirring is stirring at 60°C and 400 r / min for 240 minutes; the washing is washing 3 times with anhydrous ethanol; the vacuum drying temperature is 80°C; the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 2.4:25:0.5; and the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
[0048] In step 3), the inert atmosphere is a nitrogen atmosphere; the ultrasonic treatment is performed at a power of 400 W for 20 minutes; the heating and stirring is performed at a temperature of 65° C. and a speed of 400 r / min for 8 hours; the vacuum drying temperature is 80° C.; the mass ratio of the modified composite particles, anhydrous ethanol, sorbic acid, styrene, oleic acid and initiator is 14:50:4.0:1.6:2.4:0.18; and the initiator is azobisisobutyronitrile.
[0049] The preparation method of the protective layer comprises the following steps: mixing high-density polyethylene, modified graphene and other additives for 30 minutes, placing the mixture in an extruder and melting and extruding the mixture at a temperature of 210° C., granulating the mixture, and molding the mixture to obtain the protective layer.
[0050] Comparative Example 1 Compared with Example 4, Comparative Example 1 is different in that no zinc nitrate aqueous solution is used, and the remaining components, preparation steps and parameters are the same.
[0051] Comparative Example 2 Compared with Example 4, Comparative Example 2 is different in that no silane coupling agent is used, and the remaining components, preparation steps and parameters are the same.
[0052] Comparative Example 3 Compared with Example 4, Comparative Example 3 is different in that sorbic acid is not used, and the other components, preparation steps and parameters are the same.
[0053] Comparative Example 4 Compared with Example 4, Comparative Example 4 is different in that styrene is not used, and the other components, preparation steps and parameters are the same.
[0054] Comparative Example 5 Compared with Example 4, Comparative Example 5 is different in that oleic acid is not used, and the other components, preparation steps and parameters are the same.
[0055] The mechanical properties of the protective layer materials obtained in Examples 1-5 and Comparative Examples 1-5 were tested respectively, and the test results are shown in Table 1.
[0056] Mechanical properties test: according to GB / T 2951.11-2008; Corrosion resistance test: The sample materials of Examples 1-5 and Comparative Examples 1-5 were weighed respectively, and then the acid treatment was completely immersed in 10wt% hydrochloric acid at 60°C for 48h; the alkali treatment was completely immersed in 10wt% potassium hydroxide solution at 60°C for 48h. After the immersion, they were washed with deionized water, dried, weighed, and the weight loss rate was calculated.
[0057] Table 1
[0058] From the test results in Table 1, it can be seen that compared with comparative examples 1-5, the protective layer materials prepared in embodiments 1-5 of the present invention have excellent mechanical properties and corrosion resistance.
[0059] The present invention can provide a physical barrier through the two-dimensional structure of graphene oxide, and zinc oxide can form a more stable and effective protective layer by generating zinc salts, thereby improving the corrosion resistance of the protective layer; zinc oxide is in-situ generated on the surface of graphene oxide to form composite particles, which can improve the surface activity of graphene oxide, reduce self-agglomeration, and increase its dispersibility in the system; zinc oxide is generated on the surface of graphene oxide to effectively fill its micro-pore structure, and the combination of the two can effectively improve the structural density of the protective layer material, improve its mechanical strength and elongation at break; the present invention introduces vinyl on the surface of the composite particles by modifying the silane coupling agent, so that the composite particles can participate in the copolymerization reaction between sorbic acid, styrene and oleic acid to form an organic copolymer layer, thereby increasing the bonding force between the composite particles and the organic copolymer layer, and further improving the corrosion resistance of the protective layer. The dispersibility and compatibility of the composite particles in the polyethylene system are increased in one step, the tensile strength and elongation at break of the protective layer material are improved, a denser structure is formed, and its corrosion resistance is improved; then styrene is used to increase the grafting rate of sorbic acid and oleic acid, and the hydrogen bonds, ionic bonds, and coordination bonds between sorbic acid and oleic acid and zinc ions are combined to form a physical crosslink at one end of the organic copolymer layer, and a chemical connection is formed at the other end through a copolymerization reaction, thereby increasing the interaction between the composite particles and the polyethylene system, which is beneficial to the dispersion of the composite particles in the polyethylene system. The combination of sorbic acid and zinc ions can promote the crystallization of polyethylene to form smaller and more uniform grains. The antioxidant oleic acid, whose long carbon chain has good hydrophobicity, reduces the penetration of water molecules, and jointly improves the mechanical properties and corrosion resistance of the protective layer material.
[0060] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. An aging-resistant and corrosion-resistant flexible graphene cable, comprising a conductive wire group, a metal shielding layer and a protective layer, characterized in that: The protective layer comprises the following components by weight: 90-100 parts of high-density polyethylene, 12-16 parts of modified graphene and 2-3 parts of other additives; The preparation method of the modified graphene comprises the following steps: 1) In an inert atmosphere, slowly drop a zinc nitrate aqueous solution and a sodium hydroxide aqueous solution into graphene oxide to adjust the pH value, filter, wash, and vacuum dry to a constant weight to obtain composite particles; 2) The composite particles and anhydrous ethanol are mixed and preheated, and the silane coupling agent is added dropwise and then stirred continuously, centrifuged, washed, and vacuum dried to constant weight to obtain modified composite particles; 3) Under an inert atmosphere, the modified composite particles and anhydrous ethanol are ultrasonically mixed, sorbic acid, styrene and oleic acid are added and mixed, an initiator is added and heated and stirred, and after cooling to room temperature, the mixture is centrifuged and vacuum dried to constant weight to obtain modified graphene.
2. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: The other additives are mixed by anti-UV agent, lubricant and antioxidant in a mass ratio of 2.0-2.3:3.5-4.0:2.2-2.6; the anti-UV agent is one or two of UV-9 and BP-6; the lubricant is oxidized polyethylene wax; the antioxidant is one or more of antioxidant 168, antioxidant 1010, antioxidant 1076 and antioxidant 1098.
3. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: In step 1), the inert atmosphere is a nitrogen atmosphere; the pH value is adjusted to a pH value of 7.0-7.8; the washing is performed with deionized water until neutral; and the vacuum drying temperature is 80°C.
4. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: In step 1), the mass ratio of the zinc nitrate solution, the sodium hydroxide aqueous solution and the graphene oxide is 14-16:22-24:7.2-8.0; the concentration of the sodium hydroxide aqueous solution is 8wt%; and the concentration of the zinc nitrate aqueous solution is 6wt%.
5. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: In step 2), the preheating temperature is 40°C; the continued stirring is stirring at 50-60°C and 300-400 r / min for 180-240 min; the washing is washing with anhydrous ethanol for 3 times; and the vacuum drying temperature is 80°C.
6. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: In step 2), the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 2.0-2.4:20-25:0.4-0.5; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
7. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: In step 3), the inert atmosphere is a nitrogen atmosphere; the ultrasonic treatment is performed at a power of 300-400 W for 15-20 min; the heating and stirring is performed at a temperature of 60-65° C. and a speed of 300-400 r / min for 6-8 h; and the vacuum drying temperature is 80° C.
8. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: In step 3), the mass ratio of the modified composite particles, anhydrous ethanol, sorbic acid, styrene, oleic acid and initiator is 12-14:40-50:3.2-4.0:1.2-1.6:2.0-2.4:0.16-0.18; the initiator is azobisisobutyronitrile.
9. The aging-resistant and corrosion-resistant flexible graphene cable according to claim 1, characterized in that: The preparation method of the protective layer comprises the following steps: mixing high-density polyethylene, modified graphene and other additives for 20-30 minutes, placing the mixture in an extruder at a temperature of 190-210° C. for melt extrusion, granulating and molding the mixture to obtain the protective layer.
Citation Information
Patent Citations
Anti-aging anti-static elastomer material and preparation method thereof
CN116589850A
Ultraviolet-resistant new energy cable
CN118126470A
Surface polymerized proppants
US20210062076A1
Preparation method for graphene-based modifier, heavily-shielded network cable material containing graphene-based modifier
WO2021212898A1
Cited By
Anti-corrosion alkali-resistant offshore wind power generation cable and preparation method thereof
CN120795452A